Comparative toxicity and proliferation testing of aflibercept, bevacizumab and ranibizumab on different ocular cells. Issue 7 (17th May 2013) - Schnichels, Sven; Hagemann, Ulrike; Januschowski, Kai; Hofmann, Johanna; Bartz-Schmidt, Karl-Ulrich; Szurman, Peter; Spitzer, Martin S; Aisenbrey, Sabine
Abstract : Background/aims: Vascular endothelial growth factor (VEGF) is a key factor in the pathogenesis of neovascular retinal diseases including age-related macular degeneration. VEGF inhibitors including ranibizumab, pegaptanib or bevacizumab improve retinal morphology and vision in many patients. The recently approved drug aflibercept (VEGF Trap-Eye/Eyelea, Regeneron, Tarrytown, New York, USA) offers a new therapy modality. We therefore tested for toxic and anti-proliferating effects of aflibercept. Methods: The effects of aflibercept (0.125, 0.5, 2 mg), ranibizumab (0.125 mg) and bevacizumab (0.3125 mg) after 1, 24, 48 and 72 h on cell morphology via phase contrast pictures, cell viability via MTS assay, total cell amount via crystal violet staining, apoptosis induction via caspase 3/7 assay and proliferation via BrdU assay were investigated. Three ocular cell lines were chosen for toxicology testing: ARPE19 cells, RGC-5 cells and 661W cells. Results: Aflibercept did not cause changes in cell morphology, induce apoptosis or cause permanent decrease in cell viability, cell density or proliferation in any cell line or concentration investigated. In general, aflibercept had fewer effects (upregulation or downregulation) compared with controls than bevacizumab or ranibizumab. Conclusions: In our experiments, aflibercept did not lead to any negative effects on retinal cell lines and might therefore be used safely in clinical applications.